Ruthenium Chloride—Induced Oxidative Cyclization of Trans-Resveratrol to (±)-ε-Viniferin and Antimicrobial and Antibiofilm Activity Against Streptococcus pneumoniae - Yadav, Mukesh Kumar; Mailar, Karabasappa; Nagarajappa Masagalli, Jagadeesh; Chae, Sung-Won; Song, Jae-Jun; Choi, Won Jun (Frontiers in Pharmacology, 2019)
Polyphenol ε-viniferin (2) is a protective phytochemical found in several plant families. Here, we report a simple and effective method for the synthesis of (±)-ε-viniferin (2) as major product and (±)-(E)-ω-viniferin (3) as a minor product. Synthesized viniferin compounds and standard viniferin were analyzed for antibacterial and antibiofilm activity against Gram-positive bacteria Streptococcus pneumoniae. The minimum inhibitory concentrations (MICs) of (±)-ε-viniferin (2) and standard viniferin were 20 µm. However, the MICs of (±)-(E)-ω-viniferin (3) and compound 8 were 40 µm. Although viniferin significantly (p < 0.05) reduced pre-established in vitro biofilms and killed bacteria within the biofilm, it was unable to prevent biofilm formation at sub-MIC concentrations. The time kill experiment revealed that viniferin killed bacteria and reduced 2.8 log10 bacteria at 2 × MIC concentration after 24 h. Scanning electron microscope (SEM) analysis and live/dead biofilm staining of pre-established biofilms revealed that viniferin treatment disrupts membrane integrity of biofilm bacteria. Crystal violet absorption, total protein, and DNA and RNA release revealed that viniferin alters bacterial cell permeability, eventually killing bacteria.